2016
DOI: 10.1038/srep37372
|View full text |Cite
|
Sign up to set email alerts
|

SXT/R391 integrative and conjugative elements in Proteus species reveal abundant genetic diversity and multidrug resistance

Abstract: SXT/R391 integrative and conjugative elements (ICEs) are self-transmissible mobile genetic elements that are found in most members of Enterobacteriaceae. Here, we determined fifteen SXT/R391 ICEs carried by Proteus isolates from food (4.2%) and diarrhoea patients (17.3%). BLASTn searches against GenBank showed that the fifteen SXT/R391 ICEs were closely related to that from different Enterobacteriaceae species, including Proteus mirabilis. Using core gene phylogenetic analysis, the fifteen SXT/R391 ICEs were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…Integrative conjugative elements are auto-transferable mobile genetic elements that can be excised from the chromosome via their integrase/excisionase gene of the host bacterium and form a circular intermediate that can be transferred by conjugation (Li et al, 2016). The ICE SXT/R391 family is one of the largest ICE families with the most abundant diversity among Gramnegative bacterial species.…”
Section: Integrative Conjugative Elements (Ices)mentioning
confidence: 99%
See 1 more Smart Citation
“…Integrative conjugative elements are auto-transferable mobile genetic elements that can be excised from the chromosome via their integrase/excisionase gene of the host bacterium and form a circular intermediate that can be transferred by conjugation (Li et al, 2016). The ICE SXT/R391 family is one of the largest ICE families with the most abundant diversity among Gramnegative bacterial species.…”
Section: Integrative Conjugative Elements (Ices)mentioning
confidence: 99%
“…They carry genes coding for the resistance to sulfamethoxazole, trimethoprim, chloramphenicol, mercury, streptomycin and kanamycin, as well as β-lactamases genes [bla HMS−1 (Ryan et al, 2017), bla CMY−2 (Harada et al, 2010), bla CTX−M−2 (Mata et al, 2011)]. SXT/R391-type ICEs have been identified in strains of P. mirabilis not only in Asia (Li et al, 2016) but also in Spain (Mata et al, 2011) and in France (Aberkane et al, 2016). They are easily transferable by conjugation of P. mirabilis to E. coli, K. pneumoniae, Salmonella enterica serovar Typhimurium, or Citrobacter koseri (Harada et al, 2010) (Figures 2, 3).…”
Section: Integrative Conjugative Elements (Ices)mentioning
confidence: 99%
“…Since the extended‐spectrum β‐lactamse genes were detected in P. mirabilis in 1987 (Malekjamshidi et al., ), this multi‐antibiotic resistant bacterium has been isolated in poultry in recent years (Aragón et al., ; Lei et al., ; Li et al., ; Tonkic et al., ). The detection of many extended‐spectrum β‐lactamse genes from our isolates, which is in agreement with the results from others (Barbour et al., ; Reich et al., ; Wong et al., ), implies that the extended‐spectrum β‐lactamse genes are common in P. mirabilis isolates from poultry and may pose potential threats on public health.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, P. mirabilis has been frequently isolated from food‐producing animals, including poultry (for example, Barbour et al., ; Kim, Wei, & An, ; Lei et al., , ; Nyenje and others ; Olonitola, Fahrenfeld, & Pruden, ; Reich, Atanassova, & Klein, ; Wong, Wan, & Chen, ). Several reports have shown that this bacterium can cause foodborne illness in humans (Shi et al., ; Wang et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation